EU cohesion policy and project appraisal - Medeiros, E.; Ferreira, F. (European Planning Studies, 2025)
This paper analyses the European Union (EU) Cohesion Policy (ECP) project selection governance mechanism in eight EU Member States: Portugal, Spain, Ireland, Germany, Sweden, Czechia, Hungary, Sweden and Finland. It focuses with more detail on the implementation of the 2021–2027 ECP Integrated Territorial Instruments in Portugal. The research proposes a conceptual framework for analysing ECP project selection governance mechanism based on three main analytical dimensions: projects: (i) Relevance to development and cohesion; (ii) Multilevel Governance and Cooperation; and (iii) Sustainable Positive Territorial Impacts. By focusing mostly on the analysis of the second dimension the research concludes that the project selection governance mechanism varies slightly within EU Member States. In all cases, however, the Managing Authority of the Operational Programmes has a key role in selecting projects. In certain cases, however, like in Portugal, ECP project selection process is more complex as it requires substantial top-down verification.